Analisis Nilai Nilai Kadar Air Optimum Dan Kepadatan Kering Pada Tanah Lempung Dengan Penambahan Abu Cangkang Kemiri - Florianus Tobi Wolor; Irwan Lie Keng Wong; Helen Adry Irene Sopacua (Paulus Civil Engineering Journal, 2022)
The purpose of this study was to determine the effect of adding Candlenut Shell Ash to the maximum dry density and optimum moisture content in clay soil. Pecan shell ash as a clay soil density stabilization agent which was carried out by standard proctor testing. The research method used is Atterberg Limits testing, Moisture Content testing, Specific Gravity testing, Gradation testing (sieve analysis and hydrometer), and Compaction testing. From the characteristic tests it showed that the soil was classified as clay soil and the compaction test at point 1 and point 2 with mixed variations of 0%, 5%, 7%, 9% experienced an increase in the optimum water content. and maximum dry density. In the compaction test, 5 samples were carried out with the optimum moisture content value at point 1 of 0% variation, namely 22.855%, which continued to increase at the highest variation of 9%, namely 25.388 and at point 2, variation of 0%, namely 21.880%, continued to increase at variation of 9%, namely 24.217%, while the value of The maximum dry density at point 1 of 0% variation, which is 0.992, continues to increase at the highest variation of 9%, which is 1.058 and at point 2, variation of 0%, which is 0.957, also continues to increase at the highest variation of 9%, which is 1.047. From the results of the research conducted, it was found that Pecan Shell Ash increased the value of the optimum water content and the maximum dry density value so that it could be used to stabilize the soil.